PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - Wijaya, Leni; Edimasjar, Khodijah (Jurnal Kesehatan dan Pembangunan, 2025)
Performance is the result of work that can be achieved by an individual or group according to their respective roles and tasks in an organization. The work environment is everything that is around employees while working that can influence employees in completing the tasks and work to be done. To improve good employee performance, a good environment is also needed. The purpose of this study was to determine the effect of the work environment on employee performance at the Palembang Public Health Laboratory Center in 2025. The research design used in this study was quantitative using an analytical survey with a cross-sectional approach. The population in this study were employees at the Palembang Public Health Laboratory Center, totaling 51 employees. Sampling used a purposive sampling technique based on inclusion criteria and exclusion criteria with a sample size of 51 employees, data collection was carried out using a questionnaire which was then analyzed using statistical tests with the Chi-Square test. The results showed that there was an influence of the work environment on employee performance at the Palembang Public Health Laboratory Center with a p-value of 0.001 < ? 0.05. It is expected to maintain and improve room facilities such as adding ventilation so that employees are more comfortable working because a good working environment can improve employee performance.